Pengaruh Integrasi Teknologi Pembelajaran terhadap Efektivitas dan Transformasi Paradigma Pendidikan Era Digital - Ryan Gabriel Siringoringo; Muhamad Yanuar Alfaridzi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The digital era has significantly transformed the face of education. The integration of technology in learning through digital devices, online platforms, and multimedia resources has created a dynamic learning environment and enriched the learning experience for students. However, its implementation faces challenges such as technology access gaps, lack of technology skills among educators, data privacy issues, curriculum alignment, and negative internet content. Collaboration among stakeholders is needed to address these challenges. Technology-based education offers opportunities for improving accessibility, flexibility, personalized learning, and innovative teaching methods. Interpreting the results of technology use in education is important to optimize its benefits and formulate effective implementation strategies according to diverse educational contexts.